Menyemai Ketahanan Keluarga dalam Perspektif Spirit Hadis Rā’in - Eko Nani Fitriono; Wahdaniyah Wahdaniyah (Syamil: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This study aims to examine and formulate the concept of family resilience through the perspective of the spirit of the rā’in hadith amid the increasing problems of modern families, such as high divorce rates and domestic conflicts. This study uses a qualitative approach with library research, which examines the rā’in hadith textually, contextually, and through contextualization. The main data sources come from hadith books such as Sahih al-Bukhari and Sahih Muslim along with their commentaries, and are supported by contemporary literature related to family resilience and leadership. Research results indicate that linguistically, rā’in means a shepherd or caretaker who has full responsibility for those under his leadership. From the perspective of hadith, this concept has developed into a principle of universal leadership, as emphasized in the hadith “kullukum rā’in wa kullukum mas’ūl ‘an ra’iyyatihi,” which positions every individual as a responsible leader, including within the family scope. This hadith is authentic and is reinforced by its alignment with the values of the Qur’an, as well as explanations from scholars such as Ibn Hajar al-Asqalani, who affirmed that leadership encompasses all roles, including husband, wife, and other family members. Furthermore, this study found that the construction of family resilience can be built through three main strategies based on the spirit of the hadith rā’in, namely: (1) self-leadership as the initial foundation in forming an individual's readiness emotionally, spiritually, and socially before and during family life; (2) the synergy of roles between husband and wife as co-leaders in the family who complement each other; and (3) strengthening communication bonds grounded in the values of empathy, deliberation, and openness. These three strategies function as preventive efforts in maintaining family resilience holistically, thus being able to realize a harmonious, adaptive, and sustainable family amidst the dynamics of modern life.